A 'Communication and Patient Safety' training programme for all healthcare staff: can it make a difference?. Issue 1 (18th November 2011) - Lee, Peter; Allen, Kellie; Daly, Michael
Abstract : Communication breakdown is a factor contributing to most cases of patient harm, and this harm continues to occur at unacceptable levels. Responding to this evidence, the Metro South District of Queensland Health (Australia) has developed a communication skills training programme titled 'Communication and Patient Safety'. The three modules, each lasting 3½ h, cover both staff-to-patient and staff-to-staff communication issues, and an unusual feature is that clinical and non-clinical staff attend together. Following positive evaluation data from our initial pilot programme (involving 350 staff in a single hospital), the programme was expanded to all five hospitals in the district, and has now been completed by over 3000 staff. The results show that despite the significant time commitment, participants find the courses useful and relevant (Kirkpatrick level 1), they learn and retain new material (level 2), and they report changes in behaviour at individual, team and facility levels (level 3). Although it remains a challenge to obtain quantitative data showing that training such as this directly improves patient safety (level 4), our qualitative and informal feedback indicates that participants and their managers perceive clear improvements in the 'communication culture' after a workplace team has attended the courses. Improving 'communication for safety' in healthcare is a worldwide imperative, and other healthcare jurisdictions should be able to obtain similar results to ours if they develop and support interactive, non-didactic training in communication skills.